Mencapai Ketahanan Pangan Indonesia Berkelanjutan - Maharani, Dina Cassa (Global and Policy Journal of International Relations, 2016)
ABSTRACTProblems and challenges in achieving sustainable Indonesian food security are multi-dimensional including economic, social, political, and environmental aspects. Identification of those problems and challenges can be approached through food supply and demand analysis. From supply side, those challenges, among others, are a stiff competition in the use of natural resources, impacts of global climate change, and the dominance of smallscale farmers in food farming. From demand side, several challenges are the existence of high population growth and its dynamic characteristics, change in food consumers' preference, and competition in demand for food commodities as human consumption, feed, and energy uses. This paper aims to review current condition of Indonesian food security, to analyze challenges faced by this country, and to formulate policy alternatives in achieving sustainable Indonesian food security toward 2025. This analysis found out that in the last six years Indonesia was able to provide enough food to fulfill its people’s need, however quality of food consumption of an average Indonesian was under standard dietary pattern recommended by nutritionists. Challenges to achieve sustainable Indonesian food security toward 2025 will be more difficult. To response to the challenges, this article recommends some adjustment on policy direction of food security development, especially related to defining goals, choosing means and ways in achieving the goals, and setting targets of food security development.Keywords: sustainable food security, food demand and suplly dynamics, policy direction changesDOI : https://doi.org/10.33005/jgp.v4i02.1918